Randomisation and resource allocation: a missed opportunity for evaluating health care and social interventions - Toroyan, T. (BMJ Group, 2000)
Equipoise is widely regarded to be an essential prerequisite for the ethical conduct of a randomised controlled trial. There are some circumstances however, under which it is acceptable to conduct a randomised controlled trial (RCT) in the absence of equipoise. Limited access to the preferred intervention is one such circumstance. In this paper we present an example of a randomised trial in which access to the preferred intervention, preschool education, was severely limited by resource constraints. The ethical issues that arise when conducting randomised trials in health care are considered in the context of trials of social interventions. In health, education and social welfare, effective interventions are frequently limited due to budgetary constraints. Explicit acknowledgement of the need to ration interventions, and the use of random allocation to do this even in the absence of equipoise, would facilitate learning more about the effects of these interventions. Key Words: Randomised controlled trials • equipoise • rationing • preschool